2007
DOI: 10.1074/jbc.m605750200
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS-5 Deficiency Does Not Block Aggrecanolysis at Preferred Cleavage Sites in the Chondroitin Sulfate-rich Region of Aggrecan

Abstract: In the mouse, proteolysis in the aggrecan interglobular domain is driven by ADAMTS-5, and mice deficient in ADAMTS-5 catalytic activity are protected against aggrecan loss and cartilage damage in experimental models of arthritis. Here we show that despite ablation of ADAMTS-5 activity, aggrecanolysis can still occur at two preferred sites in the chondroitin sulfate-rich region. Retinoic acid was more effective than interleukin-1␣ (IL) in promoting cleavage at these sites in ADAMTS-5-deficient cartilage. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 58 publications
5
47
0
Order By: Relevance
“…Differential proteomic profiling of femoral head cartilage extracts and explant culture media. Previous studies using mouse femoral head cartilage to investigate aggrecanolysis used DMEM containing FCS prior to treatment with IL-1 and RetA (9,15,22). In this study, the omission of FCS was essential to identify proteins and fragments released from cartilage into the culture media and to avoid adding nonuniform levels of growth factors and cytokines.…”
Section: Resultsmentioning
confidence: 99%
“…Differential proteomic profiling of femoral head cartilage extracts and explant culture media. Previous studies using mouse femoral head cartilage to investigate aggrecanolysis used DMEM containing FCS prior to treatment with IL-1 and RetA (9,15,22). In this study, the omission of FCS was essential to identify proteins and fragments released from cartilage into the culture media and to avoid adding nonuniform levels of growth factors and cytokines.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, recombinant ADAMTS-1, -4, and -5 cleave aggrecan at 5 sites: one within the interglobular domain and four in the CS attachment region generating aggrecan fragments that match those characterized previously in bovine cartilage and synovial fluid (3,18,19). The processing of aggrecan by aggrecanases does not appear to be species-specific because the same cleavages have been reported in bovine, equine, porcine, murine, and human aggrecan (3,6,9,(22)(23)(24). The aggrecanases are initially synthesized as latent enzymes that require proteolytic modification by autolysis or the action of other proteinases as well as interaction with other matrix macromolecules to gain activity (15,(25)(26)(27)(28).…”
mentioning
confidence: 79%
“…⌬cat Mice-The generation of ADAMTS-4, ADAMTS-5, and ADAMTS-4/-5 ⌬cat mice by Cre-mediated excision of floxed exons encoding the catalytic sites has been described previously (9,22,35).…”
Section: Generation Of Adamts-4 Adamts-5 and Adamts-4/-5mentioning
confidence: 99%
See 1 more Smart Citation
“…ADAM-8 expression is increased in an animal model of asthma following allergen exposure [51] and in the bronchi of human asthmatics [48,52]. ADAMTS-4 and TS-5 are involved in the turnover of aggrecan from cartilage resulting in loss of functionality of tissue and joint disability [53][54][55][56]. Studies have indicated that ADAMTS-5 is likely the major aggrecanase in cartilage metabolism and pathology [56].…”
Section: Implication Of Adams and Adamtss In Physiology And Pathologymentioning
confidence: 99%